A Biomimetic Approach for the Creation of Two-Dimensional Microscale Surface Patterns: Creation of Isolated Immunological Synapses. (16th June 2009) - Stern, Eric; Mooney, David J.; Fahmy, Tarek M.
Abstract : Current efforts in surface functionalization have not produced a robust technique capable of creating specific two-dimensional microscale geometrical arrays composed of multiple proteins. Such a capability is desirable for engineering substrates in sensing and cell patterning applications where at least two different protein functionalities in a specific configuration are required. Here we introduce a new approach for the creation of arrays of microscale geometries. We demonstrate our approach with a biomimetic structure inspired by the immunological synapse, a cell-cell interfacial structure characterized by two concentric rings of proteins: an outer adhesion protein structure and an inner recognition ligand core. The power of the technique lies in its ability to pattern any protein in any defined geometry as well as to create arrays in parallel.